162k views
3 votes
Help me PLEASEEEEEEEEE

Help me PLEASEEEEEEEEE-example-1
User Keeva
by
5.4k points

2 Answers

1 vote

Answer:

1)12n - 56

2)6n + 21

3)-12 n -16m

4)-8m + 4

5)9 - 12y

6)-6c +12

Explanation:

6(2n - 9) = (2n x 6) (-9 x 6) = 12n - 56

3(2n + 7) = (2n x 3) (7 x 3) = 6n + 21

-4(3n+4m)= (3n x -4) (4m× -4) = -12 n -16m

-(8m -4)= -8m +4

3/4 (12 - 16y )=(12 x 0.75) (-16x 0.75) = 9 - 12y

-2(3c-6)= (3c x -2) (-6 x -2) = -6c +12

User Byako
by
5.3k points
4 votes

Answer:

I think it would be more beneficial to know how to do these then know the answers since it's quite a simple concept.

Explanation:

You take the number outside of the parentheses(if it's just a minus sign it's a negative 1) and multiply it by the number before the plus, minus, division, or multiplication sign. You multiply it by the number after. Then do the problem from there. I'll do the first one for you. 6 times 2n equals 12n. 6 times negative 9 is -54. So your answer is 12n - 54. Hope this helps.

User Larryr
by
4.6k points